Perbandingan Faktor-Faktor Yang Menentukan Pemilihan Lokasi Pedagang Perak Dan Emas Di Pasar Seni Celuk Dan Ubud - Wirawan, I Gusti Putu Nata; Wamaliya, Firmila (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 6, Juni 2014 (pp.227 - 281), 2014)
In this research aimed to compare the Factors Determining the Selection of Silver and Gold Dealer Locations in Celuk and Ubud Art Market . The sample size used in this study , at each location is 36 . Sampling in art market Celuk using proportional random sampling method and in the Ubud Market Nonproportional using random sampling methods . The data used in this penelityian is the primary data , while technical analysis is used to determine site selection factors in each place is exploratory factor analysis . The study states that the factors that determine the selection of silver and gold merchant locations in the Art Market Celuk is the first factor that is Competition / Competition and the second factor is Capital amount . Meanwhile , the factors that determine silver and gold traders in Ubud Market is the first factor is factor Facility Place of Business and the second factor is a factor Cleanliness Place of Business .
Keywords: pemilihan lokasi usaha